2016
DOI: 10.1093/nar/gkw1082
|View full text |Cite
|
Sign up to set email alerts
|

pathDIP: an annotated resource for known and predicted human gene-pathway associations and pathway enrichment analysis

Abstract: Molecular pathway data are essential in current computational and systems biology research. While there are many primary and integrated pathway databases, several challenges remain, including low proteome coverage (57%), low overlap across different databases, unavailability of direct information about underlying physical connectivity of pathway members, and high fraction of protein-coding genes without any pathway annotations, i.e. ‘pathway orphans’. In order to address all these challenges, we developed path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 33 publications
2
82
0
Order By: Relevance
“…We then identified protein–protein interactions (PPIs) among miR-194 targets using IID database V.2016–03 (http://ophid.utoronto.ca/iid), creating a PPI network that we visualised and analysed in NAViGaTOR 3.0 (http://ophid.utoronto.ca/navigator). We then performed a functional annotation and comprehensive pathway enrichment analysis of all the proteins of the network using pathDIP V.2.5 pathway database17 (http://ophid.utoronto.ca/pathDIP), using the following settings: extended pathway associations; experimentally detected PPIs; minimum confidence level for predicted protein–pathway associations: 0.99. We considered significantly enriched only pathways with q-value (false discovery rate (FDR): Benjamini-Hochberh (BH) method) lower than 0.01.…”
Section: Methodsmentioning
confidence: 99%
“…We then identified protein–protein interactions (PPIs) among miR-194 targets using IID database V.2016–03 (http://ophid.utoronto.ca/iid), creating a PPI network that we visualised and analysed in NAViGaTOR 3.0 (http://ophid.utoronto.ca/navigator). We then performed a functional annotation and comprehensive pathway enrichment analysis of all the proteins of the network using pathDIP V.2.5 pathway database17 (http://ophid.utoronto.ca/pathDIP), using the following settings: extended pathway associations; experimentally detected PPIs; minimum confidence level for predicted protein–pathway associations: 0.99. We considered significantly enriched only pathways with q-value (false discovery rate (FDR): Benjamini-Hochberh (BH) method) lower than 0.01.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical significances were reported after the Benjamini‐Hochberg (q‐value) correction for multiple comparisons. To better understand the biological relevance of the miRNAs target genes, a network analysis was executed using PathDIP (accessed 30th May 2019) . The Jaccard similarity coefficient (JC) was implemented to elucidate functional similarities between dysregulated miRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…To better understand the biological relevance of the miR-NAs target genes, a network analysis was executed using PathDIP (accessed 30th May 2019). 32 The Jaccard similarity coefficient (JC) was implemented to elucidate functional similarities between dysregulated miRNAs. This criterion was adopted to investigate the similarity of miRNAs in a pairwise manner, both in terms of their target genes and enriched pathways.…”
Section: Mirna Target Prediction and Functional Enrichment Analysismentioning
confidence: 99%
“…With advanced computational tools such that integrate all major known scoring algorithms, downstream targets may also be elucidated. Within this analysis, we demonstrated that by examining top miRNA hits from three different AML lines, we can use eigenvector centrality and hub construction to predict common downstream targets and in turn, common downstream pathways associated with AML survival [55][56][57].…”
Section: /27mentioning
confidence: 99%